Development of a questionnaire to measure reflective attitude toward conversation - Min, Byeonggon; Park, Seongseog (L1-Educational Studies in Language and Literature, 2019)
This study aimed to develop a valid questionnaire to measure upper secondary learners' Reflective Attitude toward Conversation. In the preliminary stage, 27 items were formulated under the three constructs we defined theoretically: Thoughtful Action, Content and Process Reflection, and Premise Reflection. In the exploratory stage, 467 high school students responded to the 27 items. The results of an exploratory factor analysis showed that 12 of the 27 items had good communalities (> 0.30) and good factor loadings (> 0.40). Further, the 3-factor-model showed a non-significant chi-square test result and a suitable TLI value (.979). In the confirmatory stage, 1,055 high school students responded to the 12 items finalized across two sessions. The results of the confirmatory factor analysis with the first confirmatory stage sample (568 students), showed that the NFI (.849) and CFI (.879) did not satisfy the necessary criteria (> .900). After revising two items, the results of the CFA with the second sample (487 students), revealed a CFI of .912, a GFI of .936, an RMR of .037, and an RMSEA of .076, which satisfied the necessary criteria, although the NFI of .897 still did not satisfy the necessary criterion. We recommend that future studies use the developed measure.